Bullous Mastocytosis In Infants: A Case Report - Selim Ayvacı; Malik Ergin; Özge Besci; Canan Şule Karkiner; Davi Habif; Rana İşgüder (Journal of Behçet Uz Children's Hospital, 2020)
Cutaneous mastocytosis is one of the diseases that will be considered in the differential diagnosis of patients presenting with urticarial plaques and common bullae. Its differential diagnosis should be made among other potential conditions such as bullous impetigo, bullous pemphigoid or eczematous eruptions accompanying immune deficiencies. The close follow up of evolution of specific lesions with detailed anamnesis, and physical examination the diagnosis of cutanous mastocytosis should be considered in priority. Detection of Darier's sign is also helpful during examination. Definitive diagnosis can only be established after performing a skin biopsy. Here, we present a 2.5 month-old infant with cutanous mastocytosis and discuss differential diagnosis and therapeutic features in light of current literature.